Long-Term Outcomes of Congenital Diaphragmatic Hernia: Report of a Multicenter Study in Japan - Masaya Yamoto; Kouji Nagata; Keita Terui; Masahiro Hayakawa; Hiroomi Okuyama; Shoichiro Amari; Akiko Yokoi; Kouji Masumoto; Tadaharu Okazaki; Noboru Inamura; Katsuaki Toyoshima; Yuhki Koike; et al. (MDPI AG, 2022)
Background: Treatment modalities for neonates with congenital diaphragmatic hernia (CDH) have greatly improved in recent years, with a concomitant increase in survival. However, long-term outcomes restrict the identification of optimal care pathways for CDH survivors in adolescence and adulthood. Therefore, we evaluated the long-term outcomes within the Japanese CDH Study Group (JCDHSG). Methods: Participants were born with CDH between 2006 and 2018 according to the JCDHSG. Participants were enrolled in the database at 1.5, 3, 6, and 12 years old. Follow-up items included long-term complications, operations for long-term complication, and home medical care. Results: A total of 747 patients were included in this study, with 626 survivors (83.8%) and 121 non-survivors (16.2%). At 1.5, 3, 6, and 12 years old, 45.4%, 36.5%, 34.8%, and 43.6% developed complications, and 20.1%, 14.7%, 11.5%, and 5.1% of participants required home care, respectively. Recurrence, pneumonia, pneumothorax, gastroesophageal reflux disease, and intestinal obstruction decreased with age, and thoracic deformity increased with age. Conclusions: As CDH survival rates improve, there is a need for continued research and fine-tuning of long-term care to optimize appropriate surveillance and long-term follow-up.